2019
DOI: 10.1128/jvi.01622-18
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Evidence for Lineage-Specific Differences in the Risk of Inapparent Chikungunya Virus Infection

Abstract: In late 2013, chikungunya virus (CHIKV) was introduced into the Americas, leading to widespread epidemics. A large epidemic caused by the Asian chikungunya virus (CHIKV) lineage occurred in Managua, Nicaragua, in 2015. Literature reviews commonly state that the proportion of inapparent CHIKV infections ranges from 3 to 28%. This study estimates the ratio of symptomatic to asymptomatic CHIKV infections and identifies risk factors of infection. In October to November 2015, 60 symptomatic CHIKV-infected children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 77 publications
3
35
0
1
Order By: Relevance
“…The proportion of fever with arthralgia attributable to CHIKV observed in this study (58%) is similar to previously reported ratios of symptomatic-to-asymptomatic CHIKV infection in Puerto Rico [44] and elsewhere [43, 45, 47]. Although mortality associated with CHIKV infection is rare [4851], multiple studies have reported that debilitating arthralgia and/or arthritis may occur for weeks or months after illness onset [23, 5255].…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of fever with arthralgia attributable to CHIKV observed in this study (58%) is similar to previously reported ratios of symptomatic-to-asymptomatic CHIKV infection in Puerto Rico [44] and elsewhere [43, 45, 47]. Although mortality associated with CHIKV infection is rare [4851], multiple studies have reported that debilitating arthralgia and/or arthritis may occur for weeks or months after illness onset [23, 5255].…”
Section: Discussionsupporting
confidence: 87%
“…If we assume 32.7 – 41.2% of the estimated infections are symptomatic, as previously reported in Bahia and Sergipe [53], then we estimate that the local observation success of symptomatic cases was between 12.8 – 16.1%. However, if we assume that 75 – 97% of people infected with CHIKV will develop symptomatic infections, as reported for the Indian Ocean lineage [10, 54, 55], then the chances of reported a symptomatic CHIKV case decrease to 5 – 7% [9]. Case reports suggest that the beginning of the exponential phase of the outbreak was in December 2016 ( Figure S4 ), while genetic data suggests that the outbreak clade emerged around July 2016.…”
Section: Resultsmentioning
confidence: 89%
“…Different CHIKV circulating lineages may have remarkably different public health consequences. Lineage-specific clinical presentations have been recently highlighted by a recent index cluster study which showed that 82% of CHIKV infections caused by the ECSA lineage are symptomatic, in comparison to only 52% of symptomatic infections caused by the Asian genotype [54]. While the Asian lineage seems to have circulated cryptically for 9 months before its first detection in the Caribbean [3], the faster detection of the ECSA lineage in Brazil could at least in part be a consequence of a higher rate of symptomatic to asymptomatic infections of the ECSA lineage circulating in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with African and IOL CHIKV strains, there is little or no difference in infectivity for A. aegypti, the principal urban CHIKV vector in most locations. However, based on epidemiologic [90][91][92] and animal model 87 studies, the Asian lineage strains seem to be less virulent in terms of apparent to inapparent human infection ratios and rates of chronic arthralgia. In 2013, this Asian CHIKV lineage was introduced into the Caribbean island of Saint Martin, followed by the extensive spread through much of the New World tropics and subtropics 6 .…”
Section: Geographic Spread and Founder Effectsmentioning
confidence: 99%